(untitled) (African Journal of Biomedical Research, 2024)
Traditional medicine has been a fertile source of revealing lead novel molecules which are then subjected to investigations using the techniques of the modern drug discovery. The objective of the study was to evaluate variations in serum biochemical parameters of aqueous and ethanolic extracts of Asparagus laricinus roots. The powdered plant roots material was dissolved in distilled water to prepare 2%, 10% and 20% concentration. For the second extraction. the material was also dissolved in ethanol and the increasing concentrations were controlled by varying the volumes of the solution administered. 54 Sprague Dawley rats (180g - 250g), were divided into two groups of 24 and 30 rats for aqueous and ethanolic extracts respectively. The aqueous group was further divided into four subgroups of 6 rats which were exposed ad libitum for eight weeks to 0%, 2%, 10% and 20% extracts. The ethanolic group was divided into five subgroups of 6 rats which were exposed for two weeks (via gavage) to increasing doses of 50, 100, 200 and 400mg/kg/day extracts and a control (unexposed) group. Ethanol extracts were administered daily over a period of two weeks through gavage and the control group was administered water through gavage as well. Blood samples were collected from the rats for biochemical testing. Biochemical tests were done for CHOL, BUN, CREA, ALP, AST and ALT as indicators of any possiblee damage to the tissue of organs, including the liver, kidney and spleen. Comparison of treatment groups (n=6) and controls (n=6) across all ethanol extracts showed significant differences in the starting median change in weight at the 200g/kg/day dosages as well as weight at 400g/kg/day, even though AST and ALT have high SEM values. The median change in weight remained slightly below 50g over the entire two-week period of experimentation. Biochemical results could not show any patterns in abnormalities although we observed statistically significant results on few parameters. In conclusion, the toxicological evaluation of Asparagus laricinus extracts may be considered relatively safe when given orally, as it did not produce any remarkable biochemical adverse effects in both the male and female Sprague Dawley rats